2022
DOI: 10.1093/mnras/stac1241
|View full text |Cite
|
Sign up to set email alerts
|

Timing the last major merger of galaxy clusters with large halo sparsity

Abstract: Numerical simulations have shown that massive dark matter haloes, which today host galaxy clusters, assemble their mass over time alternating periods of quiescent accretion and phases of rapid growth associated with major merger episodes. Observations of such events in clusters can provide insights on the astrophysical processes that characterise the properties of the intra-cluster medium, as well as the gravitational processes that contribute to their assembly. It is therefore of prime interest to devise a fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…To have a deeper understanding of our halo sample, we do not only focus on the median of the halo but plot the full probability density function of the relative ratios of the sparsities as in figure 1 of ref. [79]. At z = 0, there is no obvious deviation from NFW compared to the Gaussian case, but the tails of the NG+ simulation indicate a possible deviation at high redshift.…”
Section: Jcap05(2024)021mentioning
confidence: 78%
See 2 more Smart Citations
“…To have a deeper understanding of our halo sample, we do not only focus on the median of the halo but plot the full probability density function of the relative ratios of the sparsities as in figure 1 of ref. [79]. At z = 0, there is no obvious deviation from NFW compared to the Gaussian case, but the tails of the NG+ simulation indicate a possible deviation at high redshift.…”
Section: Jcap05(2024)021mentioning
confidence: 78%
“…However, it had nothing to say on whether the NFW profile is indeed a correct description of the halo density profiles in the non-Gaussian cases under consideration, which is a more profound question than the one relating to the mass-concentration relation. The halo sparsity, namely the ratio between cumulative masses enclosing two different overdensities, provides a non-parametric estimate of the halo mass distribution that encodes information beyond the simple NFW description [74][75][76][77][78][79][80]. It is defined as:…”
Section: Using Sparsity To Evaluate the Quality Of The Nfw Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many works (e.g., Neto et al 2007;Wang et al 2020) have pointed out the relation between the time spanned since the last major merger and halo concentration, 𝑐 vir = 𝑅 vir /𝑅 s , being 𝑅 s the scale radius of the Navarro et al (1997) profile (or the radius where the logarithmic slope of the DM density profile equals −2). More recently, sparsity has been suggested as a non-parametric alternative to concentration, which reduces the scatter with halo mass (Balmès et al 2014;Corasaniti et al 2018), and has also been found to correlate with the timing since the last relevant merger (Richardson & Corasaniti 2022). While sparsity is generally defined as the quotient between the masses at different spherical overdensities, we find that the one maximising the correlation with merging activity is…”
Section: Mean Radial Velocitymentioning
confidence: 99%